2001
DOI: 10.1016/s0735-1097(00)01198-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of valvular heart disease on maternal and fetal outcome of pregnancy

Abstract: Pregnancy in women with MS and AS is associated with marked increase in maternal morbidity and unfavorable effect on fetal outcome, which are related to severity of disease. Despite high maternal morbidity, mortality is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
233
3
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 370 publications
(279 citation statements)
references
References 24 publications
22
233
3
21
Order By: Relevance
“…34% of the women in our study were in NYHA class III and IV compared to 22.3% in a series by Sawhney H et al 4 Congestive cardiac failure was seen in 8 women (16%) as compared to 38% in the series by Hameed A et al and 20% in the study by Asghar F et al, arrhythmia was seen in 4% of cases, maternal mortality 10%, of which occurred in NYHA class III and IV ,this was in correspondence with Sawhney H et al who reported a maternal mortality rate of 2%, of which occurred in NYHA class III and IV. Overall cardiac complication rate in our study was 15.62% which is very similar to 13% reported by Siu SC et al 1,2,4,5 In our study 85. 6,7 All the women improved by at least one functional class by surgical intervention, compared to 82% in the Chandigarh study Sawhney H et al 4 Elkayam et al has concluded that, PBMV should be done in severe symptomatic women with MS who do not respond to medical therapy.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…34% of the women in our study were in NYHA class III and IV compared to 22.3% in a series by Sawhney H et al 4 Congestive cardiac failure was seen in 8 women (16%) as compared to 38% in the series by Hameed A et al and 20% in the study by Asghar F et al, arrhythmia was seen in 4% of cases, maternal mortality 10%, of which occurred in NYHA class III and IV ,this was in correspondence with Sawhney H et al who reported a maternal mortality rate of 2%, of which occurred in NYHA class III and IV. Overall cardiac complication rate in our study was 15.62% which is very similar to 13% reported by Siu SC et al 1,2,4,5 In our study 85. 6,7 All the women improved by at least one functional class by surgical intervention, compared to 82% in the Chandigarh study Sawhney H et al 4 Elkayam et al has concluded that, PBMV should be done in severe symptomatic women with MS who do not respond to medical therapy.…”
Section: Discussionsupporting
confidence: 89%
“…8 Preterm labour was seen in 20% in our study. The corresponding incidence in other studies was 14% Asghar F et al, 12% Sawhney H et al and 23% Hameed A et al 1,2,4 In our study, small for gestational age was seen in 16% compared to 18.2% Sawhney H et al and 21%…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations